2017
DOI: 10.1016/j.sjbs.2015.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of five antidandruff cosmetic formulations against planktonic cells and biofilms of dermatophytes

Abstract: This study aimed to investigate the antifungal effectiveness of five different formulations against dandruff and ringworm dermatophytes. was also included in our assays. Fungal susceptibility tests were performed with planktonic cells and biofilms of reference strains. Microbiological and physicochemical quality parameters were assessed for all formulations. Our data indicated that the formulations were effective against the dermatophytes strains, and to our knowledge, the effectiveness of cosmetic formulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 20 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…Some studies conducted by our group have already demonstrated the anti-biofilm activity of chalcones against fungal species such as C. gattii ( Palanco et al., 2017 ) and H. capsulatum ( Melo et al., 2017 ). Studies have been carried out to assess the anti-biofilm action of conventional drugs for treating dermatophytoses such as TRB, FLZ ( Costa-Orlandi et al., 2020 ), itraconazole, voriconazole, griseofulvin ( Brilhante et al., 2018 ), econazole ( Toukabri et al., 2018 ), and formulations of piroctone-based shampoos ( Santos; Dias-Souza, 2017 ). However, in most cases, 50 times the MIC is required to observe any biofilm inhibition ( Brilhante et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies conducted by our group have already demonstrated the anti-biofilm activity of chalcones against fungal species such as C. gattii ( Palanco et al., 2017 ) and H. capsulatum ( Melo et al., 2017 ). Studies have been carried out to assess the anti-biofilm action of conventional drugs for treating dermatophytoses such as TRB, FLZ ( Costa-Orlandi et al., 2020 ), itraconazole, voriconazole, griseofulvin ( Brilhante et al., 2018 ), econazole ( Toukabri et al., 2018 ), and formulations of piroctone-based shampoos ( Santos; Dias-Souza, 2017 ). However, in most cases, 50 times the MIC is required to observe any biofilm inhibition ( Brilhante et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm formation by T. rubrum NCPF 935 was performed based on previous method with a few modifications [16,17] The test tubes were allowed to rest at room temperature for 1 h. The gently washed using HEPES buffer after which, the biofilms were visualised at ~485 nm excitation/ ~530 nm emission (green) using a Leica TSC SP2…”
Section: Quantification Of T Rubrum Ncpf Biofilm By Safranin Stainingmentioning
confidence: 99%
“…SA as well as aspirin (acetylsalicylic acid) solutions have shown up to 90% activity against Candida albicans biofilm disruption [20]. A shampoo formulation containing SA (0.5%) in combination with zinc pyrithione (2%) has also been reported to effectively disrupt biofilms formed by Malassezia furfur and C. albicans as well as T. rubrum and T. mentagrophytes [21]. Jasmonic acid is a phytohormone with potent activity against pathogenic fungi affecting plants as well as Candida spp.…”
Section: Fungal Biofilm Inhibitorsmentioning
confidence: 99%